Explaining Government's Online Transparency on Collaborative Policy Platforms: Risk Management and Configurational Conditions. Issue 3 (3rd May 2020) - Chen, Yu-Che; Chang, Teng-Wen
Abstract: This study aims to advance our understanding of online transparency for open government by focusing on the conditions affecting the behavior of public agencies. By drawing from literature on open government, collaborative governance, and bureaucratic behavior, the study identifies key conditions for transparency. The empirical investigation builds on citizen-initiated policy proposals on an online collaborative platform and utilizes fuzzy set qualitative comparative analysis. The results support a risk-management perspective for agency-level transparency behavior. There are multiple configurations for the provision of policy and collaboration information. The lack of policy conflict is a necessary condition for information provision.